2019
DOI: 10.1016/j.apsusc.2019.07.209
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and wear resistance of (Nb,Ti)C carbide reinforced Fe matrix coating with different Ti contents and interfacial properties of (Nb,Ti)C/α-Fe

Abstract: The version presented here may differ from the published version or from the version of the record. Please see the repository URL above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The morphology of the worn surfaces was analyzed using SEM and is presented in Figure 12. The images reveal evidence of abrasion wear in all the wear tracks caused by the detachment of oxide particles formed in the coating, which start to slide along the wear track [73,75]. Delamination flakes and a smooth wear surface can also be observed in the samples.…”
Section: Wear Testmentioning
confidence: 92%
“…The morphology of the worn surfaces was analyzed using SEM and is presented in Figure 12. The images reveal evidence of abrasion wear in all the wear tracks caused by the detachment of oxide particles formed in the coating, which start to slide along the wear track [73,75]. Delamination flakes and a smooth wear surface can also be observed in the samples.…”
Section: Wear Testmentioning
confidence: 92%
“…They found a strong relationship between (Ti, Nb) C content and phase evolution, microstructure characteristics, and exothermic reaction behavior [9]. Changchun Zhao et al [10] worked on the (Nb, Ti) C reinforced Fe matrix hardfacings with different ratios of Ti prepared by gas metal arc welding (GMAW). Their results show that the grain size of NbC decreased (to 1.7 µm) and the stability of the carbide-matrix interfaces enhanced with the addition of Ti.…”
Section: Introductionmentioning
confidence: 99%
“…Examination of grains demonstrates that Nb concentration is decreasing from the core to rim (Fig.2 b) in P2-type specimens. In the literature, several studies[3,4,10,11] mention the opposite results which the core of a carbide grain predominantly containing titanium, while the rim is mostly composed of niobium. For example, Ke Yang et al[11] reported that NbC grows epitaxially from previously precipitated TiC grains.…”
mentioning
confidence: 99%
“…In a further study, Tran [11] found that the Fe atoms on the surface have three covalent bonds with the below oxygen atoms to form covalent bonds with other oxygen atoms. Zhao et al [14] reported that the wear resistance of the Fe matrix can be improved by doping Ti and Ni. The improvement in wear resistance is a result of the elements being added, which strengthens the interfacial bonding strength between the carbide and the substrate.…”
Section: Introductionmentioning
confidence: 99%